Test platform for visible light positioning - Rodrigues, Pedro Alexandre Tavares (2020)
This dissertation is addressed to location systems in indoor environments using artificial light source, based in off-the-shelf light emitting diodes, and visible light communication. It emphasizes the study of the light behaviour travelling through space and the design of a current LED driver capable of producing pulsed light. Nowadays, most of the traditional lighting systems are being replaced by LED lighting due to their energy efficiency. A study over artificial light sources is performed, specially photometry measures and their optoelectronic properties. A lighting project has been developed to adapt a dark room with the European lighting standards regulation, that follows a traditional lighting project. A linear LED current driver has been designed for regulation of LED current, continuous or pulsed mode, which allows dimming of light intensity. Light modulations have been studied for low bandwidth visible light communication system to be implemented with a microcontroller acting directly on the current that passes through the LED. The built lighting system allows, when communicating, modulation of each LED identification number through light, while performing the basic need of illumination. The modulated signals are received by photo detectors, photo diodes or image sensor (camera), which receives the signal, extracts the ID, and have the ability to measure a relative distance to the emitters, using power reception (photo diodes) or image deformation of image sensors. The adaptation of a dark room in Integrated Circuit Systems laboratory of Instituto de Telecomunicações in Aveiro, meets the necessary requirements for implementation and validation of VLP in real environments.